LA TRADUCCIÓN DE LOS ESCOLIOS A LOS IDILIOS DE TEÓCRITO DE VICENTE MARINER: ALGUNAS CONSIDERACIONES - Castro de Castro, David (Myrtia, 1996)
In 1625 Vicente Mariner de Alagón translated into Latin the scholia to Theocrit's 'Idylls'. This study deals with some characteristics of this translation and some reasons are suggested in order to explain the purpose of Mariner's work.